Silicon oxide film formation by spraying tetraethyl orthosilicate onto substrate with simultaneous low-energy SiO+ ion-beam irradiation - Satoru Yoshimura; Satoshi Sugimoto; Takae Takeuchi; Kensuke Murai; Masato Kiuchi (AIP Advances, 2023)
We attempted to deposit silicon oxide films by spraying tetraethyl orthosilicate (TEOS) onto a substrate while the substrate was also irradiated with a low-energy SiO+ ion beam. The energy of the SiO+ ions was 55 eV, and the substrate temperature was 300 °C. Following this process, we were able to deposit a film on the substrate. X-ray photoelectron spectroscopy (XPS) measurements of the film showed that it was composed of silicon oxide. XPS analysis also showed that the oxygen-to-silicon atomic concentration ratio (O/Si ratio) for the film was 1.57. For comparison, an SiO+ ion beam was used to irradiate a substrate at room temperature with simultaneous spraying of TEOS. XPS analysis of the deposited film showed that it was silicon oxide with an O/Si ratio of 1.45. In this case, however, a relatively large number of carbon atoms (7 at. %) were incorporated into the film. In both the 300 °C and room-temperature cases, we confirmed that the film deposition rate was substantially improved by supplying TEOS during SiO+ ion-beam irradiation.